Tecnologia assistiva e perfil funcional dos alunos com deficiência física nas salas de recursos multifuncionais - Queiroz, Fernanda Matrigani Mercado Gutierres de [UNESP] (2015)
The educational inclusion is worried about the learning of all the student who confronts barriers to participate effectively of the school life. In the perspective of the inclusive education the student who presents some deficiency must preferential be taken care of in common education and the special education offers the educational attendance specialized to complement its educational necessities. In this context the objective of the research shows: To analyze if the available resources of Assistive Technology in the rooms of multi-functional resources take care of the functional demand of the students with physical deficiency, according to vision of the teacher of the Specialized Educational Attendance. The study included teachers responsible for multi-purpose facilities that serve students with disabilities. For data collection the research were used instruments School Function Assessment, questionnaire of Assistive Technology for Education II and interview semi structuralized with the professors of the educational attendance specialized to identify the adequacies necessary in accordance with the specifics functional profile of the students. The collected data had been dealt with and analyzed according to analysis content and, in the sequence, carried through the triangulation of the data with the information of the three instruments already mentioned. The speech of the interviews had been organized as a descriptive summary and the information of the three collection instruments had been organized into a single document, with triangulation of data, which was analyzed according to content analysis being presented the nine categories that were generated: 1) Mobility and accessibility; 2) Movable available and used by the pupils; 3) Participation and aid in the performance of tasks; 4) Prepare and to clean 5) Pedagogical didactic material available and used by the students; 6) Use of materials; 7) Use of the computer and equipment; 8)...